2021
DOI: 10.1158/2326-6066.cir-20-0315
|View full text |Cite
|
Sign up to set email alerts
|

KIR3DL3 Is an Inhibitory Receptor for HHLA2 that Mediates an Alternative Immunoinhibitory Pathway to PD1

Abstract: Blockade of the PD1 pathway is a broadly effective cancer therapy, but additional immune-inhibitory pathways contribute to tumor immune evasion. HERV–H LTR-associating 2 (HHLA2; also known as B7H5 and B7H7) is a member of the B7 family of immunoregulatory ligands that mediates costimulatory effects through its interaction with the CD28 family member transmembrane and immunoglobulin domain containing 2 (TMIGD2). However, HHLA2 has also been known to have inhibitory effects on T cells. Here, we report that we ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 48 publications
4
74
1
Order By: Relevance
“… 12 Moreover, Rieder et al discovered that HHLA2 was insufficient to evaluate the proliferation and cytokine production of T cells stimulated with OKT3 (the anti-CD3 monoclonal antibody), which may result from the differential effects of various α-CD3 clones on T cell function. 13 Recent studies demonstrated inhibitory effects of HHLA2 on T cells and NK cells, when interacts with the inhibitory receptor KIRR3DL3, 14 suggesting HHLA2 as a potential immunotherapeutic target for cancer. In this study, we focused on the in situ distribution of HHLA2 in HCC tissue, and identified a high expression of HHLA2 on activated monocytes/macrophages in the peri-tumor region of HCC.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Moreover, Rieder et al discovered that HHLA2 was insufficient to evaluate the proliferation and cytokine production of T cells stimulated with OKT3 (the anti-CD3 monoclonal antibody), which may result from the differential effects of various α-CD3 clones on T cell function. 13 Recent studies demonstrated inhibitory effects of HHLA2 on T cells and NK cells, when interacts with the inhibitory receptor KIRR3DL3, 14 suggesting HHLA2 as a potential immunotherapeutic target for cancer. In this study, we focused on the in situ distribution of HHLA2 in HCC tissue, and identified a high expression of HHLA2 on activated monocytes/macrophages in the peri-tumor region of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that ligation of B7-H7 can either stimulate or inhibit T cell responses (2,4). In analogy to B7.1 and B7.2 that ligate CTLA-4 and CD28 to inhibit and stimulate T cell responses respectively, B7-H7 has been shown to ligate KIR3DL3 and CD28H to inhibit and stimulate T cell responses respectively (14). However, Rieder et al showed that the inhibitory effect of B7-H7 signalling is evident as early as 24 h after the initial stimulation (11).…”
Section: Discussionmentioning
confidence: 99%
“…However, Rieder et al showed that the inhibitory effect of B7-H7 signalling is evident as early as 24 h after the initial stimulation (11). Nevertheless, KIR3DL3 is not expressed on resting T cells and the expression is less than 5% upon cross-linking CD3 and CD28 (14). It is therefore plausible that other inhibitory receptors that mediate immune regulation by B7-H7 exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the cells are expressing the receptor for the target-of-interest, this can be detected by increased target binding to the surface of the cell. This approach has been successfully utilized to deorphanize secreted factors [53], interactions between immune receptors [54], or identify glycan-dependent recognition of specific ligands [55]. However, the generation and management of cDNA libraries that have significant coverage of membrane proteins can be expensive and not accessible to many investigators.…”
Section: Cell-based Library Formatsmentioning
confidence: 99%